PROVENANCE AREA OF PRECAMBRIAN QUARTZITE-SCHIST SEQUENCES OF THE KOKCHETAV MASSIF (NORTH KAZAKHSTAN) - N. A. Kanygina; A. A. Tretyakov; KE. . Degtyarev; E. V. Kovalchuk (Известия высших учебных заведений: Геология и разведка)
The results of a study of quartzite-schist sequences of the Prevendian basement of the Central and Western parts of the Kokchetav massif in the Northern Kazakhstan and ore placer deposits, confined to them, are provided. An accumulation of the both formations took place in the shelf part of the passive margin of the large continental block. Petrological and geochemical characteristics as well as the compositions of the rutile and tourmaline from palaeoplacers indicate that the clastic material came from a one distributive province. The rocks metamorphosed under the moderate and high temperatures, metasedimentary and metabasic complexes had an important role in the structure of the distributive prov-nce with the less significant role of the felsic magmatic rocks.